Socialization of the Effectiveness of Village Funds to Optimize the Financial Performance of Kebun Kelapa Village - Syaula, Maya; Ananda, Geby Citra; Farried, Annisa Ilmi; Lubis, Indah Safitri (International Conference on Sciences Development and Technology, 2023)
The results of community service activities with the title "Socialization of the Effectiveness of Village Funds to Optimize the Financial Performance of Kebun Kelapa Village". This activity aims to increase understanding and implementation of effective village financial management in the context of optimizing village funds in Kebun Kelapa Village. Through a series of steps, including need identification, outreach, training, mentoring and guidance, we succeeded in achieving significant results. Village communities, especially village officials, now have better knowledge about village financial management and transparency in the use of village funds. The positive impacts of this activity also include preparing better village financial planning, increasing village income through optimizing tax and levy revenues, as well as increasing the welfare of the people of Kebun Kelapa Village. Researchers recommend that outreach and training activities continue and be improved in other villages. Strict supervision of the use of village funds and the application of the principles of transparency and accountability in village financial management are also very important. This report reflects the successful collaboration between the service team and the Kebun Kelapa village community. Hopefully this success will be an inspiration for other villages in managing their village funds effectively and transparently.